ANALISIS FAKTOR INTERNAL YANG MEMPENGARUHI AUDIT DELAY: Dibuat Oleh Uswatun Khasanah, Muhammad Yusuf, Usamah - yusuf, muhamad; Usamah, U; khasanah, uswatun (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2021)
The purpose of this study is to determine the effect of Auditor Opinion, Profitability, Liquidity, Company Size, Age of the company to Audit Delay on real estate and property companies listed on the BEI both simultaneously and partially. The population of this study is a real estate and property company listed on the Stock Exchange in 2015 until 2017. The sample method used is Purposive Sampling with the number of companies as many as 12and 61 samples used in this study. The data used is secondary data, namely date and financial statements of real estate and property companies listed on the Indonesia Stock Exchange in 2015 until 2017. Analysis technique used in this study is multiple linier regression analysis. Based on the result of test which is tested with t test of variable profitability and company size have a significant effect to variable of Audit Delay. The variables of Auditor Opinion, Liquidity, Age of the company have no effect on audit delay. While based on simultaneous test (F test) of Auditor Opinion, Profitability, Liquidity, Company Size, and Age of the company have influence to Audit Delay. The amount of R2 in real estate and property in Indonesia amounted to 0.977 this shows the effect of independent variables ie auditor opinion, profitability, liquidity, company size, and age of the company to variable Audit Delay can be explained by this equation model of 97.7% while the remaining 2.3% influenced by other factors outside the study. Keyword: Audit Delay, Auditor Opinion, Profitability, Liquidity, Company Size, Age of the company